PENINGKATAN PEMBELAJARANIPSDENGAN MENGGUNAKAN MODELTALKING STICK DI SEKOLAH DASAR - SUSANTI, ELVA (Universitas Negeri Padang, 2014)
Abstract This research was done because teachers did not explain learning materials in details as well as did not provide opportunities to the students to give their opinions and to read the materials as a whole. This research aimed at describing the improvement of students’ social science learning outcome by using the talking stick model. The subjects of the research were thirteen fourth grade students. The result of the lesson plan analysis in cycle I was 87.49 and in cycle II was 92.85. The result of the teachers’ activities analysis in cycle I was 83.32 and in cycle II was 91.66. Meanwhile, the result of the students’ activities analysis in cycle I was 74.99 and in cycle II was 91.66. Finally, the learning outcome in cycle I was 70.89 and in cycle II was 93.24. Keywords: social science lerning process, the talking stick learning model